REPRODUCTIVE ASPECTS OF THE PRAWN Macrobrachium amazonicum IN A CONTINENTAL POPULATION LIVING DOWNSTREAM OF A HYDROELECTRIC DAM - Larissa Rosa RODRIGUES; João Alberto Farinelli PANTALEÃO; Luciana Segura de ANDRADE (Boletim do Instituto de Pesca)
The migratory behavior of females of the freshwater prawn Macrobrachium amazonicum (Heller, 1862) can indicate a strategy that optimizes the population establishment. With this idea in mind, we evaluated the reproductive biology of M. amazonicum, hypothesizing that females were evenly distributed downstream of Hydroelectric Dam. Specimens were collected monthly for one year, from six sites of Rio Grande river. The specimens were sexed and measured (carapace length; CL). A total of 14,697 adults were captured, 2,864 males (AM), 11,082 non-breeding females (AF) and 751 breeding females (BF). The smallest BF had 3.8 mm CL. The distribution of demographic groups was assessed by a Principal Component Analysis (PCA), which explained 95.16% of the distribution over the collection sites. Breeding females were more abundant in the sites closest to the dam. This result can be explained by rainfall, which varied significantly throughout the year. As the breeding females migrated upstream toward the dam and were more abundant there, our hypothesis of homogeneous distribution was rejected. This behavior probably optimizes larval dispersion. The reproduction was continuous with peaks in the period preceding the maximum rainfall.